2019
DOI: 10.15252/embj.201899430
|View full text |Cite
|
Sign up to set email alerts
|

Beclin1‐driven autophagy modulates the inflammatory response of microglia via NLRP 3

Abstract: Alzheimer's disease is characterized not only by extracellular amyloid plaques and neurofibrillary tangles, but also by microglia‐mediated neuroinflammation. Recently, autophagy has been linked to the regulation of the inflammatory response. Thus, we investigated how an impairment of autophagy mediated by BECN1/Beclin1 reduction, as described in Alzheimer's disease patients, would influence cytokine production of microglia. Acutely stimulated microglia from Becn1+/− mice exhibited increased expression of IL‐1b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 66 publications
7
122
1
Order By: Relevance
“…Interestingly, in our present study, p62 was seldom colocalized with NLRP3 after URB treatment, suggesting that p62 may be unnecessary for removing NLRP3 in the process of autophagy after URB treatment. We noticed that p62 is reported to be dispensable for removing damaged mitochondria, challenging the role of p62 in mitophagy [44][45][46]. Hence, we speculate p62-independent mitophagy might be one of the critical mechanisms involved in NLRP3 inflammasome clearance after URB treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, in our present study, p62 was seldom colocalized with NLRP3 after URB treatment, suggesting that p62 may be unnecessary for removing NLRP3 in the process of autophagy after URB treatment. We noticed that p62 is reported to be dispensable for removing damaged mitochondria, challenging the role of p62 in mitophagy [44][45][46]. Hence, we speculate p62-independent mitophagy might be one of the critical mechanisms involved in NLRP3 inflammasome clearance after URB treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Microglia, the tissue-resident macrophage population of the brain, also require autophagy to maintain their ability to phagocytose apoptotic cells, protein aggregates and debris, and its failure enhances inflammation as it occurs in macrophages [17]. Several publications show activation of primary mouse microglia or microglial cell lines after knockdown of autophagy genes (i.e., Atg5 or Atg7) [123][124][125], and characterize how the inflammatory response can be modulated by Beclin1-driven autophagy through NLRP3 degradation [126] (Figure 2).…”
Section: Cma In the Adaptive Immune Responsementioning
confidence: 99%
“…Once activated, NLRP3 would oligomerize to form inflammasome and promote maturation of caspase-1 and several proinflammatory cytokines including IL-1β and IL-18 (Shen et al, 2018). Although NLRP3 inflammasome signaling has generally been considered an immune cell-related inflammatory process (Zhou et al, 2016;Lee et al, 2018;Voet et al, 2018;Houtman et al, 2019), expression and activation of inflammasome components have also been reported in neurons (Ye et al, 2017;Teng et al, 2018;Cowie et al, 2019;Pronin et al, 2019); notably, Zhang et al (2016) demonstrated that neuronal activation of NLRP3 is involved in the pathogenesis of PD. However, the potential mechanisms regulating NLRP3 activity in PD are poorly understood.…”
Section: Introductionmentioning
confidence: 99%